1970
DOI: 10.1002/aic.690160208
|View full text |Cite
|
Sign up to set email alerts
|

Conversion and temperature profiles for complex reactions in laminar and plug flow

Abstract: An investigation of the mass and heat transfer equations describing radial and axial profiles for tubular reactors in laminar and plug flow is reported. Reactor conditions evaluated were isothermal, constant wall temperature, and adiabatic. Both diffusion and nondiffusion were considered. The reaction investigated was the demethylation of toluene in the presence of hydrogen.It was found that diffusion plays only a minor role in laminar flow for the conditions investigated. It was also found that isothermal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1971
1971
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The other limit with D t=R 2 ® ¥, gives piston flow behavior. Merill and Hamrin [1] concluded that the reactor behaves as a laminar flow reactor with no diffusion provided D t=R 2 < 3 Â 10 À3 , but we are interested in the opposite limit.…”
Section: Casementioning
confidence: 99%
“…The other limit with D t=R 2 ® ¥, gives piston flow behavior. Merill and Hamrin [1] concluded that the reactor behaves as a laminar flow reactor with no diffusion provided D t=R 2 < 3 Â 10 À3 , but we are interested in the opposite limit.…”
Section: Casementioning
confidence: 99%
“…In the literature, some relations that enable mixing efficiency estimations can be found . They are based on different measures, such as the number of layers into which the fluid stream is divided n’ , the coefficient of variation CoV, as well as different indexes of mixing effectiveness I m and σσo; however, their practical use may be difficult due to the limited number of constants available only for a few mixers’ geometries.…”
Section: Theorymentioning
confidence: 99%
“…CoV correlations have a very general form (similar to those used in the dimensional analysis), which shows the parameters that may influence the CoV but does not give a direct formula applicable for engineering (practical) calculations.…”
Section: Theorymentioning
confidence: 99%
“…Laminar flow tubular reactors (LFTRs) have received special attention since the early studies of Bosworth in 1948. Design equations for LFTRs with homogeneous reactions have been numerically solved using finite differences (Cleland and Wilhlem, 1956), series expansions (Hsu, 1965), method of the moments (Aris, 1980), Galerkin's method in the Laplace transform domain (Nigam er ul., 1982), Green's functions (Arce er ul., 1988), among many other articles (Merril and Hamrin, 1970;Subramanian er ul., 1974;Nigam and Nigam, 1980;etc.). Also, LFTRs with heterogeneous -at the wallreactions have been analyzed in several contributions (Katz, 1959;Wissler and Schechter, 1962;Smith and Carberry, 1976;inoue and Funakoshi, 1981;Vi-Doung Dang, 1983;erc.).…”
Section: Introductionmentioning
confidence: 96%